RFID for libraries : a practical approach - Neeraj Kumar (Ess Ess, 2019)
RFID, the acronym for Radio Frequency Identification, is a technology that uses radio frequency wave transmission for identifying a person or object. The use of RFID by libraries over the last few years has grown drastically. Adoption of RFID technology has enabled the libraries to take the inventory of thousands of items in their collection within days instead of months. RFID has enabled the users to check-out and return library items by themselves automatically round the clock. Besides speedy checkouts, the RFID technology helps in keeping the library collections in proper order and saves the librarians from repetitive strain injuries. RFID provides better theft control, reduces non-returns and chances of mis-shelving of a library's assets. This book examines what RFID technology is and how it works in the library scenario. The book reviews the development of RFID technology and its effects on library operations over the last couple of decades. An assessment of current implementation of the technology in libraries and the lessons learnt provide suggestions to overcome the issues faced at practical level in any library. The book also looks at the future technologies developing and how they might be applied in libraries. Presented from a library perspective this title will assist the library and information community in understanding RFID technology. The libraries planning to implement this technology can benefit from the authors' rich and practical knowledge of the subject.